Ternary positive electrode active material and preparation method thereof, secondary battery, battery module, battery pack and electric device containing the same
By co-covering modification of oxide additives and oxygen ion conductors on the high-nickel ternary layered oxide positive electrode material, the problems of material interface instability and cyclic attenuation are solved, and the electrochemical performance and service life of the battery are improved.
Patent Information
- Application Number
- CN202210017104.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-07
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-01-07
AI Technical Summary
High-nickel ternary layered oxide cathode materials have problems such as fast cycling attenuation, insufficient rate performance and unstable material interface, which affect the long battery life and safety of the battery.
Co-coated modification of the high-nickel ternary layered oxide positive electrode active material by synergistically introducing oxide additives and oxygen ion conductors, improving material interface stability and improving capacity loss problems.
It improves the electrochemical performance of the battery, enhances the cycling stability and rate performance of the material, extends the service life of the battery, and reduces oxygen release and interface side reactions.
Smart Images

Figure CN115832280B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a ternary positive electrode active material and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device containing the same. Background Art
[0002] The electrolyte plays the role of transporting ions in secondary batteries. Although it does not contribute to the battery energy, its composition directly affects many properties of secondary batteries. A large amount of experimental data shows that the interface reaction between electrodes and electrolytes and the oxidative decomposition of electrolytes under high voltages will have adverse effects on the interface stability, electrochemical performance and safety performance of secondary batteries, limiting the development of secondary batteries.
[0003] In recent years, the increasing awareness of environmental protection and the promotion of new energy vehicles have promoted the widespread application of lithium-ion batteries (LIBs) as the secondary battery system with the best comprehensive performance, and also put forward higher expectations for indicators such as the service life, energy density, safety and maintenance cost of LIBs. Among them, the development of high-performance positive electrode active materials is crucial to breaking through the bottleneck of long driving range of electric vehicles. Many positive electrode active materials (such as LiCoO2, LiNi m Co n Mn 1-m-n O2、LiNi m Co n Al 1-m-n O2, Li2Mn2O4 and LiFePO4) have been widely used, among which the high-nickel ternary layered oxide positive electrode (LiNi m Co n M 1-m-n O2, m ≥ 0.6, M = Mn, Al) has become a research hotspot in recent years due to its high reversible capacity, low cost, easy large-scale production, and low toxicity. It is considered to be the most promising new generation of high specific energy positive electrode active materials. Currently, LiNi with a nickel content of more than 90% has been synthesized. 0.9 Mn 0.1 O2 and LiNi 0.95 Co 0.025 Mn 0.025 For O2 materials, while high Ni brings capacity advantages, it is also accompanied by poor crystal thermal stability, insufficient particle chemical-mechanical stability, and unstable material interface, resulting in fast cycle decay and insufficient rate performance; residual lithium compounds (RLCs) and some impurities on the surface cause low first coulombic efficiency and poor storage performance.
[0004] Therefore, the above-mentioned technical problems need to be further resolved. Summary of the invention
[0005] In view of the above problems, the present application provides a ternary positive electrode active material and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device containing the same, and the high-nickel ternary layered oxide positive electrode active material is co-coated and modified by synergistically introducing oxide additives and oxygen ion conductors to improve the material interface stability, improve the capacity loss problem, and make the battery exhibit excellent electrochemical properties.
[0006] In the first aspect, the present application provides a ternary positive electrode active material, which includes a nickel-rich layered oxide positive electrode active material, the surface of the nickel-rich layered oxide positive electrode active material is co-coated with an oxygen ion conductor and an oxide additive; the chemical composition of the nickel-rich layered oxide positive electrode active material is LiNi x Co y A z O2, wherein A = Mn or Al, 0.6 ≤ x < 1, 0 < y ≤ 0.2, z = 1-xy.
[0007] In the technical solution of the embodiment of the present application, the oxygen ion conductor and the oxide additive are co-coated to reduce oxygen release, reduce interface side reactions, stabilize the lattice, and improve the stability of the battery. At the same time, it is also conducive to lithium ion diffusion, and the co-coating enables the high-nickel ternary electrode material to obtain good electrochemical properties.
[0008] In some embodiments, the mass ratio of the oxygen ion conductor, the oxide additive and the nickel-rich layered oxide positive electrode active material is (0.2-5): 1: 100. In the technical solution of the embodiment of the present application, the active oxygen and the release of oxygen are effectively reduced by coating the oxygen ion conductor; the oxide additive coated on the surface of the electrode material effectively reduces the corrosion of the electrolyte and the direct contact of the electrode material with other harmful substances.
[0009] In some embodiments, the chemical composition of the oxygen ion conductor is Ln m Zr 1-m O 2-δ , where Ln is a lanthanide element, 0.08<m≤0.2, 0.04<δ≤0.1. In the technical solution of the embodiment of the present application, by selecting these oxygen ion conductors, vacancies for oxygen ions can be provided, the oxygen release caused by the instability of nickel-based materials can be suppressed, the gas generation problem of the material can be alleviated, and the stability of the electrode material can be improved. The strong oxidizing elements contained in the conductors can be Ni 2+ Oxidized to Ni 3+ , thereby inhibiting the Li + / Ni 2+ The mixed arrangement of cations, together with the presence of a small amount of Zr doping (Zr-O bonds) and rare earth element doping, helps to reduce mechanical microstrain and keep the surface chemical structure stable.
[0010] In some embodiments, the lanthanide element is selected from at least one of Gd, Dy, Er, Yb and Y. In the technical solution of this embodiment, by selecting at least one of Gd, Dy, Er, Yb and Y, the Zr element in the oxygen ion conductor can be stabilized.
[0011] In some embodiments, the oxide additive is selected from at least one of TiO2, Al2O3, ZnO, SnO2 and Co3O4, and optionally, the oxide additive is selected from TiO2. In the technical solution of the embodiment of the present application, by selecting these oxide additives, the nickel-cobalt-manganese ternary positive electrode active material can be prevented from being corroded by the electrolyte, the direct contact of the electrode material with other harmful substances can be reduced, and the cycle stability of the ternary positive electrode active material can be improved.
[0012] In a second aspect, the present application provides a method for preparing a ternary positive electrode active material, comprising the following steps:
[0013] S1: adding a zirconium salt solution with a concentration of 0.05-10.0 mol / L and a dysprosium salt solution with a concentration of 0.02-3.0 mol / L to the nickel-rich layered oxide positive electrode slurry in sequence, stirring, and evenly mixing to obtain a precursor;
[0014] S2: adding the precursor obtained in step S1 and the metal esters or salts into an organic solvent in sequence, mixing, filtering, drying, ball milling, and uniformly dispersing;
[0015] S3: milling the product obtained in step S2, placing it in an oxidizing atmosphere, and sintering it at 650-950° C. for 2-6 hours to obtain the ternary positive electrode active material; the ternary positive electrode active material comprises a nickel-rich layered oxide positive electrode active material, the surface of which is co-coated with an oxygen ion conductor and an oxide additive; the chemical composition of the nickel-rich layered oxide positive electrode active material is LiNi x Co y A z O2, wherein A = Mn or Al, 0.6 ≤ x < 1, 0 < y ≤ 0.2, z = 1-xy.
[0016] The technical solution of this embodiment realizes the co-coating of oxygen ion conductor and titanium oxide by one-step sintering, inhibits the generation of highly active oxygen on the surface, reduces the release of oxygen, reduces the contact between the positive electrode active material and the electrolyte, reduces the occurrence of side reactions, reduces the residual lithium on the surface, and comprehensively improves the cycle stability of the ternary material. Introducing an appropriate amount of oxygen ion conductor on the surface can reduce Li + / Ni 2+Mixing improves the first coulombic efficiency of the material, inhibits the highly active oxygen generated by irreversible reactions on the surface, reduces oxygen release, and improves the stability of the electrode material. High-temperature sintering is used to allow zirconium doping on the surface. The stronger Zr-O bond helps to maintain the stability of the surface chemical structure.
[0017] In some embodiments, in step S1, the molar ratio of the zirconium salt to the dysprosium salt is (1-m): m, wherein 0.08 < m ≤ 0.2; the zirconium salt is selected from at least one of zirconium nitrate, zirconium oxynitrate, zirconium oxychloride and zirconium oxychloride; the dysprosium salt is selected from at least one of dysprosium nitrate hexahydrate and dysprosium nitrate hexahydrate. In the technical solution of the embodiment of the present application, by selecting these salts in this molar ratio range, it is beneficial to form a structurally stable oxygen ion conductor, so that the preparation steps of the ternary positive electrode active material are simple and easy to operate.
[0018] In some embodiments, in step S1, the ratio of the sum of the mass of the zirconium salt solution and the dysprosium salt solution to the mass of the nickel-rich layered oxide positive electrode slurry is (0.2-15):100; the mass percentage content of LiNixCoyAzO2 in the nickel-rich layered oxide positive electrode slurry is 75%-90%; the mass ratio of the zirconium salt solution to the dysprosium salt solution is (2.5-15):1. In the technical solution of the embodiment of the present application, by selecting the above ratio, the co-coating of the oxygen ion conductor and titanium oxide can be better achieved, the generation of highly active oxygen on the surface can be suppressed, and the release of oxygen can be reduced.
[0019] In some embodiments, in step S2, the mass ratio of the precursor, metal esters or salts, and organic solvent is 100:(0.2-20):(10-1000); the metal esters or salts are selected from one of tetraethyl titanate, tetrabutyl titanate, stannous chloride, stannous nitrate, tin acetate, stannous sulfate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, hydrated cobalt acetate, zinc acetate, zinc nitrate hexahydrate, aluminum sulfate and aluminum nitrate; the organic solvent is selected from at least one of ethanol, ethylene glycol, propanol, isopropanol, etc.; the zirconium salt is selected from at least one of zirconium nitrate pentahydrate, zirconium oxynitrate, zirconium dichloride and zirconium oxychloride; the dysprosium salt is selected from at least one of dysprosium nitrate hexahydrate and dysprosium nitrate hexahydrate. In the technical solution of this embodiment, by selecting these mass ratios of precursors, metal esters or salts, and organic solvents, the prepared ternary positive electrode active material can effectively resist electrolyte erosion and direct contact with other harmful substances, which is beneficial to ion transport and improves electrochemical performance.
[0020] In some embodiments, in step S3, the oxidizing atmosphere is oxygen or air, and the oxygen partial pressure of the oxidizing atmosphere is greater than 5 kPa. In the technical solution of this embodiment, by selecting the oxidizing atmosphere with an oxygen partial pressure greater than 5 kPa, a sufficient oxidizing atmosphere can be provided, which is conducive to the formation of oxides during high-temperature sintering.
[0021] In a third aspect, the present application provides a secondary battery, comprising a negative electrode plate, an electrolyte, a separator and a positive electrode plate, wherein the electrolyte and the separator are arranged between the negative electrode plate and the positive electrode plate; the positive electrode plate contains a positive electrode active material, and the positive electrode active material includes the ternary positive electrode active material in the above-mentioned embodiment.
[0022] In the technical solution of the embodiment of the present application, by using the above-mentioned ternary positive electrode active material to prepare the positive electrode plate of the secondary battery, the interface structure stability of the battery positive electrode can be improved to prevent it from being corroded by the electrolyte, etc., while at the same time making the secondary battery have stable cycle performance, good rate performance, and long high-temperature storage life.
[0023] In a fourth aspect, the present application provides a battery module, comprising the lithium-ion secondary battery in the above embodiment. The battery module can be used as a power source or energy storage device. The number of secondary batteries in the battery module can be adjusted according to the application and capacity of the battery module.
[0024] In a fifth aspect, the present application provides a battery pack, including the battery module in the above embodiment. The number and arrangement of the battery modules used in the battery pack can be determined according to actual needs. The battery pack can be used as a power source or energy storage device.
[0025] In a sixth aspect, the present application provides an electrical device, comprising the secondary battery in the above embodiment, the battery is used to provide electrical energy, and the secondary battery has a longer cycle life and a higher capacity.
[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0028] Figure 1 A schematic diagram of the structure of a vehicle according to some embodiments of the present application;
[0029] Figure 2 A schematic diagram of the structure of a lithium-ion secondary battery in some embodiments of the present application;
[0030] Figure 3 A schematic diagram of the structure of a battery module according to some embodiments of the present application;
[0031] Figure 4 A schematic diagram of the structure of a battery pack according to some embodiments of the present application;
[0032] Wherein: top cover 10; housing 11; electrode assembly 12; electrode terminal 14; tab 15; lithium ion secondary battery 100; vehicle 1000;
[0033] Battery module - 200;
[0034] Upper box-300;
[0035] Lower box-400;
[0036] Battery Pack - 500. DETAILED DESCRIPTION
[0037] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0039] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0040] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0041] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0042] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0043] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0044] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0045] In the prior art, with the development of clean energy, more and more devices use electric energy as driving energy, and then power batteries that can store more electric energy and can be charged and discharged repeatedly are rapidly developed, such as secondary batteries. Among them, power batteries are not only used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields.
[0046] [Secondary battery]
[0047] Some embodiments of the present application provide a secondary battery.
[0048] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the charge and discharge process of the battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time to allow ions to pass through. The positive electrode sheet includes a positive electrode active material, and the negative electrode sheet includes a negative electrode active material.
[0049] [Positive electrode active material]
[0050] In some embodiments of the present application, a ternary positive electrode active material is provided, which includes a nickel-rich layered oxide positive electrode active material, the surface of which is co-coated with an oxygen ion conductor and an oxide additive; the chemical composition of the nickel-rich layered oxide positive electrode active material is LiNi x Co y A z O2, wherein A = Mn or Al, 0.6 ≤ x < 1, 0 < y ≤ 0.2, z = 1-xy.
[0051] [Method for preparing positive electrode active material]
[0052] In some embodiments of the present application, a method for preparing a ternary positive electrode active material is provided, comprising: adding a zirconium salt solution with a concentration of 0.05-10.0 mol / L and a dysprosium salt solution with a concentration of 0.02-3.0 mol / L to a nickel-rich layered oxide positive electrode slurry in sequence, stirring, and uniformly mixing to obtain a precursor; adding the obtained precursor and metal esters or salts in sequence to an organic solvent, mixing, filtering, drying, ball milling, and uniformly dispersing; ball milling the obtained product and placing it in an oxidizing atmosphere, sintering at 650-950° C. for 2-6 hours to obtain the ternary positive electrode active material; the ternary positive electrode active material comprises a nickel-rich layered oxide positive electrode active material, the surface of the nickel-rich layered oxide positive electrode active material is co-coated with an oxygen ion conductor and an oxide additive; the chemical composition of the nickel-rich layered oxide positive electrode active material is LiNi x Co y A z O2, wherein A = Mn or Al, 0.6 ≤ x < 1, 0 < y ≤ 0.2, z = 1-xy.
[0053] [Positive electrode]
[0054] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the above embodiment.
[0055] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0056] In some embodiments of the present application, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0057] In some embodiments of the present application, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0058] In some embodiments of the present application, the positive electrode film layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0059] In some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0060] [Negative electrode active material]
[0061] In some embodiments of the present application, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0062] [Negative electrode]
[0063] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes the negative electrode active material of the above embodiment.
[0064] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0065] In some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0066] In some embodiments of the present application, the negative electrode film layer may further optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0067] In some embodiments of the present application, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0068] In some embodiments of the present application, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0069] In some embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0070] [Electrolytes]
[0071] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0072] In some embodiments of the present application, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0073] In some embodiments of the present application, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.
[0074] In some embodiments of the present application, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0075] In some embodiments of the present application, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0076] [Isolation film]
[0077] In some embodiments of the present application, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0078] In some embodiments of the present application, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0079] According to some embodiments of the present application, the positive electrode sheet, the negative electrode sheet and the isolation film can be made into an electrode assembly through a winding process or a lamination process.
[0080] According to some embodiments of the present application, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0081] According to some embodiments of the present application, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0082] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0083] The inventors have noticed that in lithium-ion secondary batteries, the nickel content of LiNi exceeds 90%. 0.9 Mn 0.1 O2 and LiNi 0.95 Co 0.025 Mn 0.025 In O2 positive electrode active materials, while high Ni brings capacity advantages, it is also accompanied by decreased material stability, serious interface side reactions, lattice changes during charge and discharge causing capacity decay, poor rate performance, and highly active oxygen on the lattice surface easily recombine to release oxygen. The released oxygen reacts with organic solvents to generate a large amount of heat, further leading to the deterioration of the electrochemical properties of the material, triggering thermal runaway and causing safety problems; residual lithium compounds (RLCs) and some impurities on the surface cause low initial efficiency and poor storage performance.
[0084] In order to solve the above problems, the inventors have found that the synergistic introduction of oxides and oxygen ion conductors to co-coat the high-nickel ternary layered oxide positive electrode active material can improve the material interface stability, improve the capacity loss problem, and enable the battery to exhibit excellent electrochemical properties.
[0085] The surface of high-nickel ternary layered oxides is modified by using oxygen ion conductors that have strong binding ability with oxygen atoms, which inhibits the highly active oxygen generated by the irreversible reaction on the surface, reduces oxygen release, and improves the stability of the electrode material. At the same time, the strong oxidizing elements contained in the oxygen ion conductor can 2+ Oxidized to Ni 3+ , which reduces the Li + / Ni 2+ Mixing is beneficial to improving the primary effect of the material. The modified material is synthesized by high-temperature sintering to form zirconium doping on the surface of the ternary material. The stronger Zr-O bond helps to reduce mechanical micro-strain and keep the surface chemical structure stable.
[0086] The synergistic introduction of oxide additives such as titanium oxide for coating modification can prevent the nickel-cobalt-manganese ternary positive electrode active material from being corroded by the electrolyte, and also reduce the direct contact between the electrode material and other harmful substances, thereby improving the cycle stability of the ternary material. For example, during high-temperature sintering, titanium oxide can react with residual lithium on the surface as shown in the following formulas (1) and (2), eliminating residual lithium on the surface and generating Li2TiO3, which improves the lithium ion transmission capacity and exhibits high cycle performance.
[0087] TiO2+LiOH→Li2TiO3+H2O (1)
[0088] TiO2+Li2CO3→Li2TiO3+CO2 (2)
[0089] The ternary positive electrode active material disclosed in the embodiment of the present application can be applied to a lithium-ion secondary battery, wherein the lithium-ion secondary battery comprises a negative electrode sheet, an electrolyte, a separator and a positive electrode sheet, wherein the electrolyte and the separator are arranged between the negative electrode sheet and the positive electrode sheet. The positive electrode sheet comprises a positive electrode active material, and the positive electrode active material is the ternary positive electrode active material of the above embodiment. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The ternary positive electrode active material co-coated with the surface oxygen ion conductor and titanium oxide is used to prepare the positive electrode sheet, which can improve the cycle life, rate performance and high temperature storage performance of the battery. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows ions to pass through.
[0090] The lithium ion secondary battery disclosed in the embodiment of the present application can be used in, but not limited to, electric devices such as vehicles, ships or aircraft. A power supply system comprising the lithium ion secondary battery disclosed in the present application can be used to form the electric device, which can solve the problems of material interface stability and capacity loss, and improve the high temperature storage performance and cycle life of the battery.
[0091] The embodiment of the present application provides an electric device using a lithium-ion secondary battery as a power source, and the electric device can be used for, but not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, electric bicycles, electric scooters, electric golf carts, electric trucks, electric ships, ships, spacecraft, energy storage systems, etc. Among them, electric toys can include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles, and spacecrafts, etc. The lithium-ion secondary battery is used to provide electrical energy.
[0092] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.
[0093] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A lithium-ion secondary battery 100 is disposed inside the vehicle 1000, and the lithium-ion secondary battery 100 may be disposed at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the lithium-ion secondary battery 100 may be used as an operating power source for the vehicle 1000.
[0094] Please refer to Figure 2 , Figure 2 This is a schematic diagram of the structure of a lithium-ion secondary battery provided in some embodiments of the present application. Figure 2 As shown, the lithium-ion secondary battery 100 includes a top cover 10, a housing 11, an electrode assembly 12, and an electrolyte (not shown).
[0095] The top cover 10 refers to a component that covers the opening of the shell 11 to isolate the internal environment of the lithium-ion secondary battery 100 from the external environment. Functional components such as electrode terminals 14 may be provided on the top cover 10. The electrode terminal 14 can be used to electrically connect to the electrode assembly 12 for outputting or inputting electrical energy of the lithium-ion secondary battery 100. In some embodiments, the top cover 10 may also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the lithium-ion secondary battery 100 reaches a threshold value. The material of the end cover 10 may also be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose any special restrictions on this.
[0096] The shell 11 is a component used to cooperate with the top cover 10 to form the internal environment of the lithium-ion secondary battery 100, wherein the formed internal environment can be used to accommodate the electrode assembly 12, the electrolyte and other components. The shell 11 and the top cover 10 can be independent components, and an opening can be set on the shell 11, and the internal environment of the lithium-ion secondary battery 100 is formed by covering the opening with the top cover 10 at the opening. Without limitation, the top cover 10 and the shell 11 can also be integrated. Specifically, the top cover 10 and the shell 11 can form a common connection surface before other components are put into the shell, and when the interior of the shell 11 needs to be encapsulated, the top cover 10 covers the shell 11. The material of the shell 11 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0097] The electrode assembly 12 is a component in the lithium-ion secondary battery 100 where electrochemical reactions occur. The number of electrode assemblies 12 is not limited, and the housing 11 may contain one or more electrode assemblies 12. The electrode assembly 12 is mainly formed by winding or stacking the positive electrode sheet and the negative electrode sheet, and a separator is usually provided between the positive electrode sheet and the negative electrode sheet. The parts of the positive electrode sheet and the negative electrode sheet with active materials constitute the main body of the electrode assembly 12, and the parts of the positive electrode sheet and the negative electrode sheet without active materials each constitute the tab 15. The positive tab and the negative tab may be located together at one end of the main body or at both ends of the main body respectively. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 15 connects the electrode terminals to form a current loop.
[0098] Please refer to Figure 3 , Figure 3 This is a schematic diagram of the structure of the battery module provided in some embodiments of the present application. Figure 3 As shown, the battery module 200 includes a plurality of lithium-ion secondary batteries 100, which are arranged longitudinally and can be connected in parallel. The battery module 200 can be used as a power source or energy storage device. The number of lithium-ion secondary batteries 100 in the battery module 200 can be adjusted according to the application and capacity of the battery module 200.
[0099] Please refer to Figure 4 , Figure 4 This is a schematic diagram of the structure of a battery pack provided in some embodiments of the present application. Figure 4 As shown, the battery pack 500 includes a battery module 200, an upper case 300 and a lower case 400. The upper case 300 and the lower case 400 are assembled together to form a space for accommodating the battery module 200. The battery module 200 is placed in the space of the upper case 300 and the lower case 400 assembled together. The output pole of the battery module 200 passes through one or both of the upper case 300 and the lower case 400 to supply power to the outside or charge from the outside. The number and arrangement of the battery modules 200 used in the battery pack 500 can be determined according to actual needs. The battery pack 500 can be used as a power source or an energy storage device.
[0100] According to some embodiments of the present application, the present application also provides a ternary positive electrode active material for a lithium ion secondary battery, which includes a nickel-rich layered oxide positive electrode active material, the surface of the nickel-rich layered oxide positive electrode active material is co-coated with an oxygen ion conductor and an oxide additive; the chemical composition of the nickel-rich layered oxide positive electrode active material is LiNi x Co y A z O2, wherein A = Mn or Al, 0.6 ≤ x < 1, 0 < y ≤ 0.2, z = 1-xy.
[0101] In the above technical scheme, the surface-coated oxygen ion conductor effectively inhibits the irreversible interface oxygen loss reaction in the positive electrode-electrolyte interface reaction, effectively reduces the generation of surface lattice oxygen vacancies during the cycle process, inhibits the generation and aggregation of lattice oxygen vacancies at the root, and improves the interface stability; the surface-coated oxide additive can effectively inhibit the surface dissolution of the nickel-cobalt-manganese ternary positive electrode active material, improve the interface structure stability of the ternary positive electrode active material, prevent it from being corroded by the electrolyte, etc., and at the same time react with the residual lithium on the surface to generate Li2TiO3 to improve the lithium ion transmission capacity.
[0102] According to some embodiments of the present application, optionally, the mass ratio of the oxygen ion conductor, the oxide additive and the nickel-rich layered oxide positive electrode active material is (0.2-5): 1: 100. When the amount of oxygen ion conductor introduced is small, the modification effect on the nickel-rich layered oxide positive electrode active material is not obvious; and when the amount introduced is large, due to the insufficient lithium ion transfer capacity of the oxygen ion conductor, the larger the amount of surface modification of the oxygen ion conductor, the less favorable the capacity of the battery.
[0103] According to some embodiments of the present application, optionally, the chemical composition of the oxygen ion conductor is Ln m Zr 1-m O 2-δ , where Ln is a lanthanide element, 0.08<m≤0.2, 0.04<δ≤0.1. By selecting these oxygen ion conductors, oxygen release is reduced and interface side reactions are reduced.
[0104] According to some embodiments of the present application, optionally, the lanthanide element is selected from at least one of Gd, Dy, Er, Yb and Y. By selecting at least one of Gd, Dy, Er, Yb and Y, the Zr element in the oxygen ion conductor can be stabilized.
[0105] According to some embodiments of the present application, optionally, the oxide additive is selected from one of TiO2, Al2O3, ZnO, SnO2 and Co3O4, preferably TiO2, which can better eliminate residual lithium. A uniform oxide coating layer (similar to a core-shell coating structure) is formed on the basis of not changing the crystal structure of the ternary material and not forming an obvious impurity phase, which has better cycle stability, thermal stability and other performance improvements.
[0106] According to some embodiments of the present application, optionally, the co-coating thickness of the oxygen ion conductor and the oxide additive on the surface of the nickel-rich layered oxide positive electrode active material is 2-35 nm. If the co-coating thickness is less than 2 nm, it cannot be completely coated, and the electrolyte and harmful substances cannot be effectively isolated; if the co-coating thickness is greater than 35 nm, it is not conducive to the transmission of ions and electrons, and the electrochemical performance is reduced.
[0107] According to some embodiments of the present application, the present application also provides a method for preparing a ternary positive electrode active material for a lithium ion secondary battery, comprising the following steps:
[0108] S1. A zirconium salt solution with a concentration of 0.05-10.0 mol / L and a dysprosium salt solution with a concentration of 0.02-3.0 mol / L are sequentially added to the nickel-rich layered oxide positive electrode slurry and stirred. After uniform mixing, a precursor containing water on the surface is obtained;
[0109] S2: adding the precursor obtained in step S1 and metal esters or salts into an organic solvent in sequence, mixing, hydrolyzing, filtering, and drying;
[0110] S3: milling the product obtained in step S2, placing it in an oxidizing atmosphere, and sintering it at 650-950° C. for 2-6 hours to obtain the ternary positive electrode active material; the ternary positive electrode active material comprises a nickel-rich layered oxide positive electrode active material, the surface of which is co-coated with an oxygen ion conductor and an oxide additive; the chemical composition of the nickel-rich layered oxide positive electrode active material is LiNi x Co y A z O2, wherein A = Mn or Al, 0.6 ≤ x < 1, 0 < y ≤ 0.2, z = 1-xy.
[0111] In the above technical scheme, the nickel-rich layered oxide positive electrode active material is coated on the surface, and a titanium oxide and oxygen ion conductor co-coating layer with a thickness of 2 to 35 nm is formed in situ by sintering, so that the cycle performance of the nickel-rich positive electrode active material can be stabilized, the capacity can be improved, and the electrochemical performance can be improved. The ball milling is to make the material dispersed evenly, and the hydrolysis products of metal esters or salts generate oxide additives in an oxidizing atmosphere. The oxide additive can prevent the nickel-cobalt-manganese ternary positive electrode active material from being corroded by the electrolyte, reduce the direct contact between the electrode material and other harmful substances, and improve the cycle stability of the ternary material. During the high-temperature sintering process, titanium oxide can also react with residual lithium (LiOH, Li2CO3) on the surface, eliminating the residual lithium on the surface and generating Li2TiO3, which can improve the lithium ion transmission capacity and show high cycle performance.
[0112] According to some embodiments of the present application, in step S1, optionally, the molar ratio of the zirconium salt to the dysprosium salt is (1-m):m, wherein 0.08<m<0.2. If the molar ratio of the zirconium salt to the dysprosium salt is lower than the lower limit, the coating rate is low, the modification effect is not obvious, and the stability and the reduction of oxygen release cannot be effectively modified; if the molar ratio of the zirconium salt to the dysprosium salt is higher than the upper limit, the coating is too thick, the ion transmission, and the electrochemical performance are reduced.
[0113] According to some embodiments of the present application, in step S1, optionally, the zirconium salt is selected from at least one of zirconium nitrate, zirconium oxynitrate, zirconium oxychloride and zirconium oxychloride; the dysprosium salt is selected from at least one of dysprosium nitrate hexahydrate and dysprosium nitrate hexahydrate. These salts are easily soluble, have stable structures and are easy to prepare. Selecting these salts facilitates the coating of oxygen ion conductors.
[0114] According to some embodiments of the present application, in step S1, optionally, the ratio of the sum of the mass of the zirconium salt solution and the dysprosium salt solution to the mass of the nickel-rich layered oxide positive electrode slurry is (0.2-15): 100. If the aforementioned ratio is less than 0.2:100, the coating rate is small, the modification effect is not obvious, and the stability and the reduction of oxygen release cannot be effectively modified; if the aforementioned ratio is greater than 15:100, the coating is too thick, ion transmission, and electrochemical performance are reduced.
[0115] According to some embodiments of the present application, in step S1, optionally, the mass percentage content of LiNixCoyAzO2 in the nickel-rich layered oxide positive electrode slurry is 75%-90%. If the mass percentage content of LiNixCoyAzO2 is less than 75%, the amount of nickel-rich layered oxide positive electrode active material is insufficient, so that the capacity of the battery finally prepared does not meet the requirements; if the mass percentage content of LiNixCoyAzO2 is greater than 90%, the co-coating modification effect of titanium oxide and oxygen ion conductor is insufficient.
[0116] According to some embodiments of the present application, in step S1, optionally, the mass ratio of the zirconium salt solution to the dysprosium salt solution is (2.5-15): 1. This ratio range is conducive to forming a structurally stable oxygen ion conductor.
[0117] According to some embodiments of the present application, in step S1, optionally, the precursor is a water-containing precursor, wherein the mass ratio of the precursor to water is (1.2-3): 1; for the subsequent metal esters or salts to select titanate compounds, the surface contains water in order to prevent the subsequent hydrolysis of the titanate compounds from being insufficient, which may result in insufficient hydrolysis and inability to synthesize the corresponding titanium oxide, and excessive water may make subsequent drying difficult. When the water content is within this range, the complete hydrolysis of the titanate compounds can be guaranteed. Titanates need to be hydrolyzed to form Ti(OH)4 and then sintered to form TiO2. Others do not have the ability to hydrolyze, and ammonia water needs to be added to adjust the pH to generate the corresponding oxide coating in the subsequent sintering step.
[0118] According to some embodiments of the present application, the stirring speed in step S1 is maintained at 400-1000r / s, and the stirring time is 0.5h-6h. This arrangement is to better disperse the zirconium salt solution and the dysprosium salt solution in the nickel-rich layered oxide positive electrode slurry. If the rotation speed is lower than 400r / s, the grinding medium is not fully brought to a certain height, and the material can only be ground and crushed by the weak sliding between the media; when the rotation speed is higher than 1000r / s, the ground material adheres to the inner wall of the mill and moves in a circle with the mill, and the purpose of the medium effectively impacting the material is not achieved. The above-mentioned grinding medium is a corundum ball with a particle size of 20-60mm.
[0119] According to some embodiments of the present application, in step S2, optionally, the mass ratio of the precursor, metal esters or salts, and organic solvent is 100: (0.2-20): (10-1000). If the mass ratio of the above three is lower than the lower limit of the range, the oxygen ion conductor coating rate is low, and the active oxygen and oxygen release cannot be effectively reduced; the oxide coated on the surface of the electrode material is small and the corrosion of the electrolyte cannot be effectively reduced, and the electrode material is in direct contact with other harmful substances; if the mass ratio of the above three is higher than the upper limit of the range, the oxygen ion conductor and the oxide coating are too thick, which is not conducive to the transmission and conduction of lithium ions and electrons, resulting in reduced electrochemical performance.
[0120] According to some embodiments of the present application, in step S2, optionally, the metal ester or salt is selected from one of tetraethyl titanate, tetrabutyl titanate, stannous chloride, stannous nitrate, stannous acetate, stannous sulfate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, hydrated cobalt acetate, zinc acetate, zinc nitrate hexahydrate, aluminum sulfate and aluminum nitrate. The organic solvent is selected from at least one of ethanol, ethylene glycol, propanol, isopropanol, etc.; the zirconium salt is selected from at least one of zirconium nitrate pentahydrate, zirconium oxynitrate, zirconium oxychloride and zirconium oxychloride; the dysprosium salt is selected from at least one of dysprosium nitrate hexahydrate and dysprosium nitrate hexahydrate. The above-mentioned metal esters or salts are easily soluble and easy to obtain, and can be sintered at high temperature to form the desired product.
[0121] According to some embodiments of the present application, in step S3, optionally, the oxidizing atmosphere is oxygen or air, and the oxygen partial pressure of the oxidizing atmosphere is greater than 5 kPa. If the oxygen partial pressure is lower than 5 kPa, sufficient oxygen cannot be provided, and oxides cannot be synthesized during high-temperature sintering.
[0122] The present application is further described below in conjunction with specific embodiments.
[0123] Example 1
[0124] (1) Preparation of positive electrode sheet
[0125] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and dysprosium nitrate hexahydrate, wherein n(Zr(NO3)4·5H2O):n(Dy(NO3)4·6H2O)=8:2, m(zirconium oxynitrate pentahydrate+dysprosium nitrate hexahydrate):m(nickel-rich layered oxide)=9.88:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1, and then the precursor is mixed with tetrabutyl titanate in anhydrous ethanol to undergo hydrolysis reaction and then filtered, m(tetrabutyl titanate):m(precursor)=4.26:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C, and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 3wt% and 1wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-30nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Dy 0.2 O 1.9 .
[0126] The co-coated nickel-rich layered oxide positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 1.
[0127] (2) Preparation of negative electrode sheet
[0128] Active material artificial graphite, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium hydroxymethyl cellulose (CMC) were dry-mixed evenly in a weight ratio of 96.5:1:1:1.5, deionized water was added to make the solid content reach 70%, and the mixture was mixed evenly to prepare a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode collector copper foil with a thickness of 0.15 mm, dried in an oven at 100°C, cold pressed to a thickness of 0.1 mm under a pressure of 50t, and cut to make the mold width reach 63 mm to finally obtain a negative electrode sheet.
[0129] (3) Preparation of electrolyte
[0130] In an argon atmosphere glove box (H2O<0.01ppm, O2<0.01ppm), the organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 4 / 6, 12.5wt% (based on the weight of the electrolyte) of LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred evenly to obtain the electrolyte of Example 1.
[0131] (4) Isolation film
[0132] A polyethylene film is used as the isolation film.
[0133] (5) Preparation of lithium-ion secondary batteries
[0134] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried battery, and then vacuum packaging, standing, forming, shaping and other processes are carried out to obtain a lithium-ion secondary battery.
[0135] Example 2
[0136] (1) Preparation of positive electrode sheet
[0137] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and dysprosium nitrate hexahydrate, wherein n(Zr(NO3)4·5H2O):n(Dy(NO3)4·6H2O)=8:2, m(zirconium oxynitrate pentahydrate+dysprosium nitrate hexahydrate):m(nickel-rich layered oxide)=9.88:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, wherein m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 3wt% and 2wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-35nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Dy 0.2 O 1.9 .
[0138] The co-coated nickel-rich layered oxide positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 2.
[0139] The other steps are the same as those in Example 1.
[0140] Example 3
[0141] (1) Preparation of positive electrode sheet
[0142] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and dysprosium nitrate hexahydrate, wherein n(Zr(NO3)4·5H2O):n(Dy(NO3)4·6H2O)=8:2, m(zirconium oxynitrate pentahydrate+dysprosium nitrate hexahydrate):m(nickel-rich layered oxide)=9.88:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, m(tetrabutyl titanate):m(precursor)=12.78:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 3wt% and 3wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-40nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Dy 0.2 O 1.9 .
[0143] The co-coated nickel-rich layered oxide positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 1.
[0144] The other steps are the same as those in Example 1.
[0145] Example 4
[0146] (1) Preparation of positive electrode sheet
[0147] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and dysprosium nitrate hexahydrate, wherein n(Zr(NO3)4·5H2O):n(Dy(NO3)4·6H2O)=8:2, m(zirconium oxynitrate pentahydrate + dysprosium nitrate hexahydrate):m(nickel-rich layered oxide)=1.65:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, wherein m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 0.5wt% and 2wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-20nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Dy 0.2 O 1.9 .
[0148] The co-coated nickel-rich layered oxide positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 5.
[0149] Example 5
[0150] (1) Preparation of positive electrode sheet
[0151] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and dysprosium nitrate hexahydrate, wherein n(Zr(NO3)4·5H2O):n(Dy(NO3)4·6H2O)=8:2, m(zirconium oxynitrate pentahydrate + dysprosium nitrate hexahydrate):m(nickel-rich layered oxide)=3.29:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, wherein m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 1 wt% and 2 wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-25 nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Dy 0.2 O 1.9 .
[0152] The co-coated nickel-rich layered oxide positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to make the mold width reach 60 mm to obtain the positive electrode sheet of Example 5.
[0153] Example 6
[0154] (1) Preparation of positive electrode sheet
[0155] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and dysprosium nitrate hexahydrate, wherein n(Zr(NO3)4·5H2O):n(Dy(NO3)4·6H2O)=8:2, m(zirconium oxynitrate pentahydrate + dysprosium nitrate hexahydrate):m(nickel-rich layered oxide)=6.58:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, wherein m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 2wt% and 2wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-30nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Dy 0.2 O 1.9 .
[0156] The co-coated nickel-rich positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 5.
[0157] Example 7
[0158] (1) Preparation of positive electrode sheet
[0159] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and dysprosium nitrate hexahydrate, wherein n(Zr(NO3)4·5H2O):n(Dy(NO3)4·6H2O)=8:2, m(zirconium oxynitrate pentahydrate + dysprosium nitrate hexahydrate):m(nickel-rich layered oxide)=13.17:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, wherein m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 4wt% and 2wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-40nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Dy 0.2 O 1.9 .
[0160] The co-coated nickel-rich layered oxide positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to make the mold width reach 60 mm to obtain the positive electrode sheet of Example 5.
[0161] Example 8
[0162] (1) Preparation of positive electrode sheet
[0163] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and ytterbium nitrate pentahydrate, wherein n(Zr(NO3)4·5H2O):n(Yb(NO3)3·5H2O)=8:2, m(zirconium oxynitrate pentahydrate + ytterbium nitrate pentahydrate):m(nickel-rich layered oxide)=9.42:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, m(tetrabutyl titanate):m(precursor)=4.26:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 3wt% and 1wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-30nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Yb 0.2 O 1.9 .
[0164] The co-coated nickel-rich positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 5.
[0165] Example 9
[0166] (1) Preparation of positive electrode sheet
[0167] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and ytterbium nitrate pentahydrate, wherein n(Zr(NO3)4·5H2O):n(Yb(NO3)3·5H2O)=8:2, m(zirconium oxynitrate pentahydrate+ytterbium nitrate pentahydrate):m(nickel-rich layered oxide)=9.42:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 3wt% and 2wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-35nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Yb 0.2 O 1.9 .
[0168] The co-coated nickel-rich layered oxide positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 4.
[0169] The other steps are the same as those in Example 1.
[0170] Example 10
[0171] (1) Preparation of positive electrode sheet
[0172] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and ytterbium nitrate pentahydrate, wherein n(Zr(NO3)4·5H2O):n(Yb(NO3)3·5H2O)=8:2, m(zirconium oxynitrate pentahydrate + ytterbium nitrate pentahydrate):m(nickel-rich layered oxide)=9.42:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, m(tetrabutyl titanate):m(precursor)=12.78:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 3wt% and 3wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-40nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Yb 0.2 O 1.9 .
[0173] The co-coated nickel-rich positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 5.
[0174] Embodiment 11
[0175] (1) Preparation of positive electrode sheet
[0176] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and ytterbium nitrate pentahydrate, wherein n(Zr(NO3)4·5H2O):n(Yb(NO3)3·5H2O)=8:2, m(zirconium oxynitrate pentahydrate + ytterbium nitrate pentahydrate):m(nickel-rich layered oxide)=1.57:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, wherein m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 0.5wt% and 2wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-20nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Yb 0.2 O 1.9 .
[0177] The co-coated nickel-rich positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 5.
[0178] Example 12
[0179] (1) Preparation of positive electrode sheet
[0180] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and ytterbium nitrate pentahydrate, wherein n(Zr(NO3)4·5H2O):n(Yb(NO3)3·5H2O)=8:2, m(zirconium oxynitrate pentahydrate + ytterbium nitrate pentahydrate):m(nickel-rich layered oxide)=3.14:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 1 wt% and 2 wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-25 nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Yb 0.2 O 1.9 .
[0181] The co-coated nickel-rich positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 5.
[0182] Example 13
[0183] (1) Preparation of positive electrode sheet
[0184] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and ytterbium nitrate pentahydrate, wherein n(Zr(NO3)4·5H2O):n(Yb(NO3)3·5H2O)=8:2, m(zirconium oxynitrate pentahydrate + ytterbium nitrate pentahydrate):m(nickel-rich layered oxide)=6.28:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 2wt% and 2wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-30nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Yb 0.2 O 1.9 .
[0185] The co-coated nickel-rich positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 5.
[0186] Embodiment 14
[0187] (1) Preparation of positive electrode sheet
[0188] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and ytterbium nitrate pentahydrate, wherein n(Zr(NO3)4·5H2O):n(Yb(NO3)3·5H2O)=8:2, m(zirconium oxynitrate pentahydrate + ytterbium nitrate pentahydrate):m(nickel-rich layered oxide)=12.56:100, and the surface water-containing precursor is obtained after uniform mixing, and the mass ratio of the precursor to water is controlled to be 2:1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, wherein m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain a nickel-rich layered oxide positive electrode active material co-coated with an oxygen ion conductor and titanium oxide, with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor and titanium oxide account for 4wt% and 2wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material, respectively. The co-coating thickness of the oxygen ion conductor and titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-40nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Yb 0.2 O 1.9 .
[0189] The co-coated nickel-rich positive electrode active material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) prepared by the above method are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to a mold width of 60 mm to obtain the positive electrode sheet of Example 5.
[0190] Comparative Example 1
[0191] (1) Preparation of positive electrode sheet
[0192] An unmodified nickel-rich layered oxide (whose particle size Dv50 is 5-10 μm) is directly used as the positive electrode active material, and the unmodified nickel-rich layered oxide, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to make the mold width reach 60 mm. This is the positive electrode sheet of Comparative Example 1.
[0193] The other steps are the same as those in Example 1.
[0194] Comparative Example 2
[0195] (1) Preparation of positive electrode sheet
[0196] The nickel-rich layered oxide is mixed with zirconium oxynitrate pentahydrate and dysprosium nitrate hexahydrate, wherein n(Zr(NO3)4·5H2O):n(Dy(NO3)4·6H2O)=8:2, m(zirconium oxynitrate pentahydrate+dysprosium nitrate hexahydrate):m(nickel-rich layered oxide)=9.4208:100, and after being uniformly mixed, it is dried at 80°C and ball-milled (ball-milling time is 60min, ball-milling speed is 1000r·min -1 ) and then sintered at 700°C for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa) to obtain an oxygen ion conductor-coated nickel-rich layered oxide positive electrode active material with a particle size Dv50 of 5-20 μm, wherein the oxygen ion conductor accounts for 3 wt% of the mass percentage of the nickel-rich layered oxide positive electrode active material. The coating thickness of the oxygen ion conductor on the surface of the nickel-rich layered oxide positive electrode active material is 2-25 nm. The chemical composition of the oxygen ion conductor is Zr 0.8 Dy 0.2 O 1.9 .
[0197] The oxygen ion conductor Zr prepared by the above method 0.8 Dy 0.2 O 1.9 The coated nickel-rich ternary material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and solvent N-methylpyrrolidone (NMP) are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to make the mold width reach 60 mm to obtain the positive electrode sheet of Comparative Example 2.
[0198] The other steps are the same as those in Example 1.
[0199] Comparative Example 3
[0200] (1) Preparation of positive electrode sheet
[0201] Water is added to the nickel-rich layered oxide to obtain a surface-water-containing precursor, and the mass ratio of the precursor to water is controlled to be (1.2-3):1. The precursor is then mixed with tetrabutyl titanate in anhydrous ethanol to undergo a hydrolysis reaction and then filtered, m(tetrabutyl titanate):m(precursor)=8.52:100, m(anhydrous ethanol):m(precursor)=1:1, and then dried at 80°C and ball milled (ball milling time is 60min, ball milling speed is 1000r·min -1) and then sintered at 700° C. for 5 hours in an air atmosphere (oxygen partial pressure of 5 kPa), the nickel-rich layered oxide positive electrode active material coated with titanium oxide has a particle size Dv50 of 5-20 μm, wherein the mass percentage of titanium oxide in the nickel-rich layered oxide positive electrode active material is 2 wt %. The coating thickness of titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is 2-20 nm.
[0202] The nickel-rich layered oxide positive electrode active material prepared by the above method, the conductive agent carbon black, the binder polyvinylidene fluoride (PVDF), and the solvent N-methylpyrrolidone (NMP) are fully stirred and mixed in a weight ratio of 8:0.8:1.2:10 to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on the positive electrode collector with a coating thickness of 0.15 mm, dried at 100°C, cold pressed to 0.1 mm under a pressure of 50t, and cut to make the mold width reach 60 mm to obtain the positive electrode sheet of Comparative Example 3.
[0203] The other steps are the same as those in Example 1.
[0204] The particle size Dv50 mentioned above refers to the particle size range corresponding to 50% of the volume distribution of the measured material.
[0205] Test Case
[0206] Capacity test method: After standing still at 25℃, let it stand for 5 minutes, charge to 4.3V with 0.3C constant current, charge to 4.3V with 0.1C constant voltage, let it stand for 5 minutes, discharge to 2.5V with 0.3C constant current, let it stand for 5 minutes, discharge to 2.5V with 0.1C constant voltage, let it stand for 5 minutes, then the capacity value can be measured.
[0207] Cycle test method: After standing still at 25°C, let it stand for 5 minutes, charge to 4.3V at 0.3C constant current, charge to 4.3V at 0.1C constant voltage, let it stand for 5 minutes, discharge to 2.5V at 0.3C constant current, let it stand for 5 minutes, discharge to 2.5V at 0.1C constant voltage, let it stand for 5 minutes, record the maximum number of cycles of normal battery (no diving).
[0208] Gas production test method: fill with oil gauge; stand at 25℃ for 5 minutes, then discharge at 0.33C constant current to 2.8V, stand for 10 minutes, then charge at constant current to 4.19V, then charge at constant voltage to 0.05C and stand for 5 minutes, charge to 97% SOC and store at constant temperature in a 60℃ high temperature box. The oil gauge monitors the internal gas pressure of the battery cell, and stops the test when it reaches 0.4MPa, and records the number of days.
[0209] The co-coating thickness of the oxygen ion conductor or titanium oxide on the surface of the nickel-rich layered oxide positive electrode active material is characterized by TEM. The mass percentage of the oxygen ion conductor or titanium oxide in the nickel-rich layered oxide positive electrode active material is measured by ICP-MS.
[0210] The main parameters for preparing the positive electrode sheets of Examples 1-14 and Comparative Examples 1-3 of the present application are shown in Table 1.
[0211] The following tests were conducted on the coulombic efficiency, first discharge gram capacity, discharge gram capacity after 300 cycles, capacity retention rate after 300 cycles, capacity retention rate after 1000 cycles, and cycle stability number of the lithium ion secondary batteries of Examples 1-14 of the present application and Comparative Examples 1-3. The test results are shown in Table 2.
[0212] Table 1
[0213]
[0214]
[0215] Table 2
[0216]
[0217] From the data in Tables 1 and 2, it can be seen that compared with Comparative Examples 1-3, the high nickel ternary materials co-coated with oxygen ion conductors and oxides prepared in Examples 1-14 not only improve the battery life, discharge capacity, long cycle capacity retention rate and cycle stability, but also reduce the gas generation during the cycle. 0.8 Dy 0.2 O 1.9 The effect of slowing down the release of oxygen is better. In Examples 1-7, when the oxygen ion conductor is co-coated with titanium oxide and 2 wt% of titanium oxide is co-coated with 3% of oxygen ion conductor, it has a better effect on slowing down the generation of gas and maintaining the structural stability during the cycle.
[0218] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A ternary positive electrode active material, comprising a nickel-rich layered oxide positive electrode active material, wherein the surface of the nickel-rich layered oxide positive electrode active material is co-coated with an oxygen ion conductor and an oxide additive; the chemical composition of the nickel-rich layered oxide positive electrode active material is LiNi x Co y A z O2, where A = Mn or Al, 0.6 ≤ x < 1, 0 < y ≤ 0.2, z = 1-xy; The chemical composition of the oxygen ion conductor is Ln m Zr 1-m O 2-δ , where Ln is a lanthanide element, 0.08<m≤0.2, 0.04<δ≤0.
1.
2. The ternary positive electrode active material according to claim 1, characterized in that: The mass ratio of the oxygen ion conductor, the oxide additive and the nickel-rich layered oxide positive electrode active material is (0.2-5):1:
100.
3. The ternary positive electrode active material according to claim 2, characterized in that: The lanthanide element is selected from at least one of Gd, Dy, Er, Yb and Y.
4. The ternary positive electrode active material according to claim 1, characterized in that: The oxide additive is selected from one of TiO2, Al2O3, ZnO, SnO2 and Co3O4.
5. The ternary positive electrode active material according to claim 4, characterized in that: The oxide additive is selected from TiO2.
6. A method for preparing the ternary positive electrode active material according to any one of claims 1 to 5, comprising the following steps: S1: adding a zirconium salt solution with a concentration of 0.05-10.0 mol / L and a dysprosium salt solution with a concentration of 0.02-3.0 mol / L to the nickel-rich layered oxide positive electrode slurry in sequence, stirring, and evenly mixing to obtain a precursor; S2: adding the precursor obtained in step S1 and the metal esters or salts into an organic solvent in sequence, mixing, filtering, drying, ball milling, and uniformly dispersing; S3: milling the product obtained in step S2, placing it in an oxidizing atmosphere, and sintering it at 650-950° C. for 2-6 hours to obtain the ternary positive electrode active material; the ternary positive electrode active material comprises a nickel-rich layered oxide positive electrode active material, the surface of which is co-coated with an oxygen ion conductor and an oxide additive; the chemical composition of the nickel-rich layered oxide positive electrode active material is LiNi x Co y A z O2, where A=Mn or Al, 0.6≤x<1, 0<y≤0.2, z=1-xy.
7. The method for preparing the ternary positive electrode active material according to claim 6, characterized in that: In step S1, the molar ratio of the zirconium salt to the dysprosium salt is (1-m): m, wherein 0.08<m≤0.2; the zirconium salt is selected from at least one of zirconium nitrate, zirconium oxynitrate, zirconium oxychloride and zirconium oxychloride; and the dysprosium salt is selected from dysprosium nitrate hexahydrate.
8. The method for preparing the ternary positive electrode active material according to claim 6, characterized in that: In step S1, the ratio of the sum of the masses of the zirconium salt solution and the dysprosium salt solution to the mass of the nickel-rich layered oxide positive electrode slurry is (0.2-15):100; the mass ratio of the zirconium salt solution to the dysprosium salt solution is (2.5-15):
1.
9. The method for preparing the ternary positive electrode active material according to claim 6, characterized in that: In step S2, the mass ratio of the precursor, the metal ester or salt, and the organic solvent is 100:(0.2~20):(10~1000); the metal ester or salt is selected from one of tetraethyl titanate, tetrabutyl titanate, stannous chloride, stannous nitrate, tin acetate, stannous sulfate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, hydrated cobalt acetate, zinc acetate, zinc nitrate hexahydrate, aluminum sulfate and aluminum nitrate; the organic solvent is selected from at least one of ethanol, ethylene glycol, propanol, and isopropanol; the zirconium salt is selected from at least one of zirconium nitrate pentahydrate, zirconium oxynitrate, zirconium dichloride and zirconium oxychloride; the dysprosium salt is selected from dysprosium nitrate hexahydrate.
10. A secondary battery, characterized in that: It comprises a negative electrode plate, an electrolyte, a separator and a positive electrode plate, wherein the electrolyte and the separator are arranged between the negative electrode plate and the positive electrode plate; the positive electrode plate contains a positive electrode active material, and the positive electrode active material comprises the ternary positive electrode active material according to any one of claims 1 to 5. 11 . A battery module comprising the secondary battery according to claim 10 .
12. A battery pack comprising the battery module according to claim 11.
13. An electrical device comprising the secondary battery according to claim 10.
Citation Information
Patent Citations
Anode active material, preparation method of anode active material, high-performance anode slurry containing anode active material, and all-solid-state lithium ion battery
CN106784798A
Double-oxide co-coated high-nickel lithium battery positive electrode material and preparation method thereof
CN108390039A